2006
DOI: 10.1002/cne.21089
|View full text |Cite
|
Sign up to set email alerts
|

Distinct perisynaptic and synaptic localization of NMDA and AMPA receptors on ganglion cells in rat retina

Abstract: At most excitatory synapses, AMPA and NMDA receptors (AMPARs and NMDARs) occupy the postsynaptic density (PSD) and contribute to miniature excitatory postsynaptic currents (mEPSCs) elicited by single transmitter quanta. Juxtaposition of AMPARs and NMDARs may be crucial for certain types of synaptic plasticity, although extrasynaptic NMDARs also may contribute. AMPARs and NMDARs also contribute to evoked EPSCs in retinal ganglion cells (RGCs), but mEPSCs are mediated solely by AMPARs. Previous work indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 92 publications
7
83
0
Order By: Relevance
“…Our loss-of-function experiments show that this non-cell-autonomous mechanism accounts for Ͼ60% of the NMDA-induced neuronal loss in the retina. Given the prevalence of NMDA receptors on retinal neurons (Zhang and Diamond, 2006), direct action of NMDA may play a modest, yet tangible, role in excitotoxicity in this system. However, our findings are a departure from the traditional paradigm of excitotoxic damage in which the death of neurons was entirely attributed to excessive Ca 2ϩ influx via neuronal NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Our loss-of-function experiments show that this non-cell-autonomous mechanism accounts for Ͼ60% of the NMDA-induced neuronal loss in the retina. Given the prevalence of NMDA receptors on retinal neurons (Zhang and Diamond, 2006), direct action of NMDA may play a modest, yet tangible, role in excitotoxicity in this system. However, our findings are a departure from the traditional paradigm of excitotoxic damage in which the death of neurons was entirely attributed to excessive Ca 2ϩ influx via neuronal NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Because glutamate is released at the mitral cell dendritic synapses, as a postsynaptic marker we used an antibody to the GluR2 and GluR3 subunits of the AMPA receptor (Isaacson and Strowbridge, 1998). Previous ultrastructural work has shown that the GluR2/3 subunits are located in the postsynaptic density in established synaptic circuits in the rat EPL and rat retina (Sassoe-Pognetto and Ottersen, 2000;Zhang and Diamond, 2006). In the EPL, puncta immunoreactive for GluR2/3 were heavily distributed.…”
Section: Synapse Formationmentioning
confidence: 99%
“…We found that DHPG increased calcium within neurons in the GCL and increased the excitability of cultured RGCs by suppressing a background K ϩ conductance. Retinal ganglion cells are driven mainly by glutamatergic input from bipolar cells, mediated by synaptic ␣-amino-3-hydroxyl-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and synaptic or extrasynaptic N-methyl-D-aspartate receptors (NMDARs) (Chen and Diamond 2002;Matsui et al 1998;Sagdullaev et al 2006;Zhang and Diamond 2006). Given the role of group I mGluRs at other CNS glutamatergic synapses, our findings suggest a potential additional contribution of group I mGluRs at the bipolar to ganglion cell synapse.…”
Section: Introductionmentioning
confidence: 99%